2004
DOI: 10.1515/hf.2004.040
|View full text |Cite
|
Sign up to set email alerts
|

The creep of wood destabilized by change in moisture content. Part 1: The creep behaviors of wood during and immediately after drying

Abstract: To better understand mechano-sorptive creep, creep behaviors were compared in wood samples during the drying process, immediately after drying, and after a long conditioning under constant humidity and temperature. Creep was greater in the sample tested immediately after drying than in the sample conditioned for a long time under relative humidity equal to that after drying, despite the fact that these samples had almost the same moisture content (MC). While the wood that has been moisture-conditioned for a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Wu and Milota investigated the tangential MS deformations of Douglas fir in both desorption and absorption processes [4,5]. Takahashi et al found that the creep behaviors of Japanese cypress are different during the drying process, immediately after drying, and after a long period of conditioning under constant humidity and temperature [6]. Perre and Passard proposed a comprehensive model to predict drying stress evolution based on MS creep at different temperature levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Milota investigated the tangential MS deformations of Douglas fir in both desorption and absorption processes [4,5]. Takahashi et al found that the creep behaviors of Japanese cypress are different during the drying process, immediately after drying, and after a long period of conditioning under constant humidity and temperature [6]. Perre and Passard proposed a comprehensive model to predict drying stress evolution based on MS creep at different temperature levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, for the nearly steady-state S 1 , where temperature was lower and RH was constant, V-C strain did not easily recover, whereas, for the non-steadystate S 2 , where temperature was higher and RH and MC varied significantly, V-C strain recovered easier and produced reverse V-C strain. Theoretically, compared with the steady-state, the creep is large for the non-steady-state (Takahashi et al 2004(Takahashi et al , 2005(Takahashi et al , 2006. This is the main cause for the differences in creep between the two schedules.…”
Section: Variation Of V-c Strain Characteristicsmentioning
confidence: 99%
“…A lot of investigations concentrated on the experimental determination and analytical expressions of the mechano-sorptive creep (Mukudai and Yata 1988;Hunt 1989;Toratti and Svensson 2000;Navi et al 2002;Takahashi et al 2004Takahashi et al , 2005Takahashi et al , 2006Dong et al 2010;Kaboorani et al 2013;Violaine et al 2015). However, the pure visco elastic creep is usually neglected in numerical models and received much less attention compared to the mechanosorptive effects (Liu 1993).…”
Section: Introductionmentioning
confidence: 99%